Infrastructure for Testing and Diagnosing Multimedia Devices - Hahanov, V. I.; Mostova, K.; Paschenko, O. (EWDTS, 2011)
In this paper HW/SW systems testing and faults diagnosing approach is described, also method for effective faults detection and defects localization within the systemunder-test is proposed. Essential increase of consumer requirements for complex electronic devices leads to substantial growth of complexity for HW and SW components, services, and system interfaces. Such tendency increases the importance to provide high quality for HW, SW, and networking components and services. One of the main goals which comes to the foreground of industry is to decrease the cost of exploitation by creating the standardized infrastructures for maintenance which providing service exploitation, testing, disposal and, elimination of functional defects. Well known rule of ten for hardware components stating that fault detection cost increases in ten times on the next following design or manufacturing stages. Nowadays fast growing complexities of hardware is transforming this rule into rule of twenty which makes even more important to detect the fault on early design stages, rather then on chip/PCB manufacturing, or system assembling stages. Goal of this work is to develop method which increases product quality by means of developing sufficient HW/SW test and diagnosis approach, also decreasing faults detection and defects localization time in order to improve system performance on example of multimedia devices.
Keywords: Infrastructure for Testing; Diagnosing Multimedia Devices; HW/SW systems